Characterizing therapist delivery of evidence-based intervention strategies in publicly funded mental health services for children with autism spectrum disorder: Differentiating practice patterns in usual care and AIM HI delivery. (August 2021) - Hurwich-Reiss, Eliana; Chlebowski, Colby; Lind, Teresa; Martinez, Kassandra; Best, Karin M; Brookman-Frazee, Lauren
This study identified patterns of therapist delivery of evidence-based intervention strategies with children with autism spectrum disorder within publicly funded mental health services and compared patterns for therapists delivering usual care to those trained in AIM HI ("An Individualized Mental Health Intervention for ASD"). Data were drawn from a randomized community effectiveness trial and included a subsample of 159 therapists (86% female) providing outpatient or school-based psychotherapy. Therapist strategies were measured via observational coding of psychotherapy session recordings. Exploratory factor analysis used to examine patterns of strategy delivery showed that among therapists in the usual care condition, strategies loaded onto the single factor, General Strategies, whereas for therapists in the AIM HI training condition, strategies grouped onto two factors, Autism Engagement Strategies and Active Teaching Strategies . Among usual care therapists, General Strategies were associated with an increase in child behavior problems, whereas for AIM HI therapists, Active Teaching Strategies were associated with reductions in child behavior problems over 18 months. Results support the effectiveness of training therapists in evidence-based interventions to increase the specificity of strategies delivered to children with autism spectrum disorder served in publicly funded mental health settings. Findings also support the use of active teaching strategies in reducing challenging behaviors. Lay abstract: This study was conducted to identify patterns of therapist delivery of evidence-based intervention strategies with children with autism spectrum disorder receiving publicly funded mental health services and compare strategy use for therapists delivering usual care to those trained to deliver AIM HI ("An Individualized Mental Health Intervention for ASD"), an intervention designed to reduce challenging behaviors in children with autism spectrum disorder. For therapists trained in AIM HI, intervention strategies grouped onto two factors, Autism Engagement Strategies and Active Teaching Strategies, while strategies used by usual care therapists grouped onto a broader single factor, General Strategies . Among usual care therapists, General Strategies were related to an increase in child behavior problems, whereas for AIM HI therapists, Active Teaching Strategies were related with reductions in child behavior problems over 18 months. Findings support the use of active teaching strategies in reducing challenging behaviors in children with autism spectrum disorder and provide support for the effectiveness of training therapists in evidence-based interventions to promote the delivery of targeted, specific intervention strategies to children with autism spectrum disorder in mental health services.